Integrating Electric Buses and Diverse Charging Technologies for Sustainable Public Transportation - Elkholy, Sama (2024)
A Master of Science thesis in Electrical Engineering by Sama Elkholy entitled, “Integrating Electric Buses and Diverse Charging Technologies for Sustainable Public Transportation”, submitted in May 2024. Thesis advisor is Dr. Mostafa Shaaban. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).